Culture and technology a primer - Slack, Jennifer Daryl; Wise, J. Macgregor (John Macgregor) (New York Peter Lang, 2015)
Culture and Technology is an essential guide to that debate and its fascinating history. It is a primer for beginners and an invaluable resource for those deeply committed to understanding the new digital culture. The award-winning first edition (2005) has been comprehensively updated to incorporate new technologies and contemporary theories about them.
The power and problem of culture, the power and problem of technology -- Progress -- Convenience -- Determinism -- Control -- Luddism -- Appropriate technology -- The Unabomber -- Meaning -- Causality -- Agency -- Articulation and assemblage -- Politics and economics -- Space and time -- Identity -- Critical conjunctures.
Revised edition of Culture + technology / Jennifer Daryl Slack, J. Macgregor Wise. 2005.
Includes bibliographical references (pages 243-257) and index.
Keywords: Technology -- Philosophy; Technology -- Social aspects; Technology and civilization